Hypoxia inducible factor-1ɑ as a potential therapeutic target for osteosarcoma metastasis - Zhou, Jianghu; Lan, Fengjun; Liu, Miao; Wang, Fengyan; Ning, Xu; Yang, Hua; Sun, Hong (Frontiers in Pharmacology, 2024)
Osteosarcoma (OS) is a malignant tumor originating from mesenchymal tissue.Pulmonary metastasis is usually present upon initial diagnosis, and metastasis is the primary factor affecting the poor prognosis of patients with OS. Current research shows that the ability to regulate the cellular microenvironment is essential for preventing the distant metastasis of OS, and anoxic microenvironments are important features of solid tumors. During hypoxia, hypoxia-inducible factor-1α (HIF-1α) expression levels and stability increase. Increased HIF-1α promotes tumor vascular remodeling, epithelial-mesenchymal transformation (EMT), and OS cells invasiveness; this leads to distant metastasis of OS cells. HIF-1α plays an essential role in the mechanisms of OS metastasis. In order to develop precise prognostic indicators and potential therapeutic targets for OS treatment, this review examines the molecular mechanisms of HIF-1α in the distant metastasis of OS cells; the signal transduction pathways mediated by HIF-1α are also discussed.